Risk for cancer development in familial Mediterranean fever and associated predisposing factors: an ambidirectional cohort study from the international AIDA Network registries - Vitale, Antonio; Caggiano, Valeria; Tufan, Abdurrahman; Ragab, Gaafar; Batu, Ezgi Deniz; Portincasa, Piero; Aragona, Emma; Sota, Jurgen; Conti, Giovanni; De Paulis, Amato; Rigante, Donato; Olivieri, Alma Nunzia; et al. (Frontiers in Immunology, 2024)
Objective: Inflammation has been associated with an increased risk for cancer development, while innate immune system activation could counteract the risk for malignancies. Familial Mediterranean fever (FMF) is a severe systemic inflammatory condition and also represents the archetype of innate immunity deregulation. Therefore, the aim of this study is to investigate the risk for cancer development in FMF. Methods: The risk ratio (RR) for malignancies was separately compared between FMF patients and fibromyalgia subjects, Still’s disease patients and Behçet’s disease patients. Clinical variables associated with cancer development in FMF patients were searched through binary logistic regression. Results: 580 FMF patients and 102 fibromyalgia subjects, 1012 Behçet’s disease patients and 497 Still’s disease patients were enrolled. The RR for the occurrence of malignant neoplasms was 0.26 (95% Confidence Interval [CI.] 0.10-0.73, p=0.006) in patients with FMF compared to fibromyalgia subjects; the RR for the occurrence of malignant cancer was 0.51 (95% CI. 0.23-1.16, p=0.10) in FMF compared to Still’s disease and 0.60 (95% CI. 0.29-1.28, p=0.18) in FMF compared to Behçet’s disease. At logistic regression, the risk of occurrence of malignant neoplasms in FMF patients was associated with the age at disease onset (β1=0.039, 95% CI. 0.001-0.071, p=0.02), the age at the diagnosis (β1=0.048, 95% CI. 0.039-0.085, p=0.006), the age at the enrolment (β1=0.05, 95% CI. 0.007-0.068, p=0.01), the number of attacks per year (β1=0.011, 95% CI. 0.001- 0.019, p=0.008), the use of biotechnological agents (β1=1.77, 95% CI. 0.43-3.19, p=0.009), the use of anti-IL-1 agents (β1=2.089, 95% CI. 0.7-3.5, p=0.002). Conclusions: The risk for cancer is reduced in Caucasic FMF patients; however, when malignant neoplasms occur, this is more frequent in FMF cases suffering from a severe disease phenotype and presenting a colchicine-resistant disease.